Analyzing the concept of disruptive behavior in healthcare work: an integrative review* - Roberta Meneses Oliveira; Lucilane Maria Sales da Silva; Maria Vilani Cavalcante Guedes; Adriana Catarina de Souza Oliveira; Rosario Gómez Sánchez; Raimundo Augusto Martins Torres
Abstract OBJECTIVE To analyze the concept of disruptive behavior in healthcare work. METHOD An integrative review carried out in the theoretical phase of a qualitative research substantiated by the theoretical framework of the Hybrid Model of Concept Development. The search for articles was conducted in the CINAHL, LILACS, PsycINFO, PubMed and SciVerse Scopus databases in 2013. RESULTS 70 scientific articles answered the guiding question and lead to attributes of disruptive behavior, being: incivility, psychological violence and physical/sexual violence; with their main antecedents (intrapersonal, interpersonal and organizational) being: personality characteristics, stress and work overload; and consequences of: workers' moral/mental distress, compromised patient safety, labor loss, and disruption of communication, collaboration and teamwork. CONCLUSION Analysis of the disruptive behavior concept in healthcare work showed a construct in its theoretical stage that encompasses different disrespectful conduct adopted by health workers in the hospital context, which deserve the attention of leadership for better recognition and proper handling of cases and their consequences.